Prinsip-Prinsip Komunikasi Islam Dalam Masyarakat Muslim Desa Budaya Budaya Lingga,Kec.Simpang Empat, Kab.Karo - Afriadi Amin; Abdul Karim Batu Bara; Najiah Maisaro Br Nst (Universitas Muhammadiyah Enrekang, 2022)
Humans are essentially never far from social relations with the environment with communication because communication between communities and religious communities can be well established. Likewise with communication to fellow religious people, especially to Islamic communication. Islamic communication is often a discipline that is applied in minority communities in several areas, especially to invite people to the path of ALLAH SWT and in its application always emphasizes religious values ​​and does not escape social and cultural values ​​without neglecting the values ​​of Islam itself. Islamic communication in a highly cultured society always emphasizes the principles of Islamic communication and the methods in accordance with the Qur'an and Hadith. The principles of Islamic communication itself are not only conveying messages but also as an arena for changing social behavior and also establishing harmonious communication and also holding hands between Muslim communities and Islamic communication and the principles of Islamic communication itself.